Using a well-to-well interplay during the CO2 huff-n-puff process for enhanced oil recovery in an inclined oil reservoir: Experiments, simulations, and pilot tests - Hao, Hongda; Hou, Jirui; Qu, Ming; Guo, Wenmin; Deng, Song; Liu, Huaizhu (Frontiers in Energy Research, 2023)
A well-to-well interplay of CO2 huff-n-puff is proposed as a novel gas injection strategy for displacing interwell remaining oil in a well pair in an inclined oil reservoir. The well-to-well interplay mechanisms for enhanced oil recovery (EOR) are firstly studied in laboratory using a three dimensional (3D) physical model. Different CO2 injection schemes are designed according to different well locations, and the production performance including oil, water and gas rates are used for the EOR evaluation. Then, a sensitivity analysis of the well-to-well interplay is studied using a numerical model, and geological, developmental and fluidic factors are considered in the simulations. The experimental results show that when CO2 is injected into a lower well, a higher well can always be benefit with an oil increment. Under the effects of gravity segregation and edge-water driving, the injected CO2 at the lower position can move upward to a higher position, where a large proportion of crude oil is remained between wells after natural edge-water flooding. The oil recovery of the well-to-well interplay is 2.30% higher than the conventional CO2 huff-n-puff in the laboratory. Numerical results show that CO2 injection mass, stratigraphic dip, horizontal permeability and interwell spacing are the most influencing factors for the well-to-well interplay, and an application criterion for the well-to-well interplay is then proposed based on the simulations. Pilot tests using the well-to-well interplay of CO2 huff-n-puff were widely applicated in C2-1 Block, Jidong Oilfield, China, since the year of 2010. A total of 2.27×104m3 of crude oil was recovered until the end of 2018, and the oil/CO2 exchange ratio was as high as 3.92. The well-to-well interplay not only extracted the interwell remaining oil effectively, but also achieved a higher CO2 utilization efficiency. The finding of this study can help for a better understanding of EOR mechanisms using the well-to-well interplay during CO2 huff-n-puff process in an inclined oil reservoir.